Coexistence of Paget disease and lung cancer - importance of patient management - Manevska, Nevena; Jankulovska, Anamarija; Stefanovski Todorova, Dusica; Makazlieva, Tanja; Stojanoski Sinisa (Discover STM Publishing Ltd., 2022)
Background: The coexistence of metabolic bone disease, such as Paget disease (PD) and malignant tumor is frequently described in patients with breast, prostate, lung, lymphoproliferative, colorectal, and renal neoplasms. Indeed, when evaluating cancer patients, there may be diagnostic dilemma of interpreting some changes in bone involvement, whether they are malignant or metabolic changes, since some radiological features of metabolic bone disease can mimic those of bone metastases. Case Presentation: We report a case of 55-year-old male patient, with diagnosed lung adenocarcinoma, referred to the Nuclear Medicine Department for a bone scintigraphy (BS), for evaluation of presented bone metastasis. The Single photon emission computed tomography (SPECT)/computer tomography (CT) scan revealed intensive metabolic accumulation of the radiotracer in cervical vertebra C7, and thoracic vertebra Th1, Th6, Th11, Th12, as well as lumbar vertebra L4, L5, left sacroiliac joint, both iliac and pubic bones and left proximal femur. The FDG PET/CT showed diffuse, but mildly increased uptake in Тh6, Тh11, L4, L5 and pelvic bones (SUV max = 3.3). The CT revealed destruction of Th11 body with compression fracture. Diagnosis of PD was made based on the findings of BS and PET/CT and further confirmed on bone biopsy and the patient was started with bisphosphonate therapy. Conclusion: BS and SPECT/CT are of great importance in accurate detection of incidental PD in patients with lung cancer.
Keywords: Bone scan; SPECT/C; bone metastasis; Paget disease; lung cancer